FOOD SECURITY ASPECTS REVIEW FROM FOOD SECURITY ASPECTS AND RICE AVAILABILITY DURING THE COVID-19 PANDEMIC IN CENTRAL JAVA. - Dewi Sitoresmi N.K.A; Didit Purnomo (Jurnal Ekonomi, 2022)
Food security is an important factor to ensure human survival, especially with increasing population growth and ever-increasing agricultural land. There are several things that affect food security such as food availability, food availability, benefits and other factors such as land area, food production rate and per capita income. This study aims to find out the effect of food availability, availability and utilization on food security indices in Central Java during the Covid-19 pandemic and to see food availability in terms of production in rice in Central Java before the pandemic and during the Covid-19 pandemic. This study used a descriptive quantitative method with the data analysis technique used was a hypothesis test. The subjects used in this study are 29 regencies in Central Java, the data used are secondary data derived from Central Java BPS and the annual report of the Food Security Office. Research results show that the amount of rice production during the pandemic decreased significantly compared to rice products before the pandemic. As the amount of production decreased, the amount of rice imports during the pandemic increased. Related to the availability relationship, the range and utilization of panga in Central Java has a significant and simultaneous effect on the food security index in Central Java.